التظاهرات الجلدية للداء السكري - دلّول, محمود; خدّام, جمال; زريق, بديع (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 156 مريضاً مصاباً بالداء السكري لديهم تظاهرة جلدية واحدة أو أكثر، كُشفت من خلال فحص سريري شامل للجلد، وتم إجراء عيار سكر الدم الصباحي على الريق ودراسة السجل الطبي للمرضى الداخليين في قسم الأمراض الباطنية. النتائج: تراوحت أعمار معظم مرضى الدراسة بين 40-60 سنة. وجد لدى 98 مريضاً تظاهرة جلدية واحدة للداء السكري، ولدى 40 مريضاً تظاهرتان، و12مريضاً 3 تظاهرات و6 مرضى 4 تظاهرات فقط. شكلت الأخماج الجلدية التظاهرة الجلدية الأكثر تواتراً، وكانت الحكة هي التظاهرة الجلدية الأكثر شيوعاً بعد الأخماج الجلدية. وجدت زيادة في حدوث التظاهرات الجلدية لدى مرضى النمط الثاني للداء السكري، كما لوحظ أنه كلما طالت فترة الإصابة بالداء السكري ازداد احتمال حدوث التظاهرات الجلدية المرافقة. Atotal of 156 diabetic patients displaying one or more dermatological manifestations were identified and thoroughly examined for any skin disorder. For diabetes we had measured the fasting glucose titers, and for internal patients it was obtained from the medical records. Results: most of the diabetic patients who developed cutaneous manifestations were between 40- 60 years old. Of the 156 patients, 98 had only 1 cutaneous manifestation, 40 had 2, 12 had 3 and 6 had 4. Skin infections were the major cutaneous manifestations; the second most common presenting symptom was pruritus. Patients with diabetes mellitus type2 were found to have increasing rate of cutaneous manifestations. As the duration of diabetes mellitus increases, the probability of developing cutaneous manifestations increases too.